Revolutionizing Healthcare: The Impact of AI on Precision Medicine - Nori, Lakshmi Prasanthi; Lohitha, Maddala; Vadapalli, Rama Rao; Bonthagarala, Brahmaiah; Nagineni, Sudarshan Rao; Kalidindi, Venkateswara Raju (International Journal of Pharmaceutical Investigation, 2025)
Artificial Intelligence (AI) is ushering in a transformative era for personalized medicine by customizing therapeutic interventions based on individual patient profiles, including genetic information and environmental influences. Through the analysis of intricate biological datasets, AI significantly improves diagnostic accuracy, prognostic assessments and therapeutic planning, thereby enabling more precise patient stratification and enhanced clinical outcomes. This advancement is particularly evident in the realms of genomic analysis and pharmacogenomics. Nonetheless, the integration of AI into healthcare introduces substantial legal and ethical considerations. Foremost among these are concerns related to data privacy, security and equitable access to treatment. It is imperative to address these issues to effectively leverage the full potential of AI. Achieving this requires a reevaluation of regulatory frameworks and an enhancement of training programs for healthcare professionals. As AI continues to advance within the healthcare sector, it promises to fundamentally redefine disease management and prevention, heralding a new epoch of medical innovation.
Keywords: Personalized medicine; Artificial intelligence; Pharmacogenomics; Regulatory framework; Diagnosis